Optical monitoring of gas supply systems in metropolitan area - Domański, Andrzej W.; Sierakowski, Marek W.; Woliński, Tomasz R. (Photonics Letters of Poland, 2011)
A novel fiber optic sensor system to monitor the gas pipeline network designed for PGNiG, Polish oil and gas exploration and production company is presented. The system is based on standard telecommunication fibers and devices, except for user-oriented and specially designed intensity-based optical sensors that utilize fiber macro- and microbending effects. Laboratory tests showed that the system is simple, easy to install, reliable, and fulfils the user requirements. Full Text: PDF References L. Zou, G. Ferrier, S. Afshar, Q. Yu, L. Chen, X. Bao,"Distributed Brillouin Scattering Sensor for Discrimination of Wall-Thinning Defects in Steel Pipe under Internal Pressure", App. Opt. 43, 1583 (2004)[CrossRef] L. Zou, X. Bao, S. Yang, L. Chen, F. Ravet,"Effect of Brillouin slow light on distributed Brillouin fiber sensors", Opt. Lett. 31, 2698 (2006)[CrossRef] D. Marcuse,"Microdeformation losses of single-mode fibers", Appl. Opt. 23, 1082 (1984)[CrossRef] R. Olshansky,"Distortion losses in cabled optical fibers", Appl. Opt. 14, 20 (1975) A.W. Domański, T. Poczęsny, K. Prokopczuk, P. Makowski,"An optical fiber loop sensor for vibration monitoring", Phot. Lett. Poland 2(2), 58 (2010) T. Poczęsny, K. Prokopczuk, P. Makowski, A.W. Domański,"Optical fiber macro-bend seismic sensor for real-time vibration monitoring in harsh industrial environment", Proc. SPIE 8082, 80823L (2011)[CrossRef] K. Prokopczuk, T. Poczęsny, A.W. Domański,"Multi-point vibration sensor using a fiber optic telecommunication cable", Proc. SPIE 8010, 80100E (2011)[CrossRef]